Morning resistance exercise and cricket-specific repeated sprinting each improve indices of afternoon physical and cognitive performance in professional male cricketers. Issue 2 (February 2022) - Nutt, Fergus; Hills, Samuel P.; Russell, Mark; Waldron, Mark; Scott, Phil; Norris, Jonty; Cook, Christian J.; Mason, Billy; Ball, Nick; Kilduff, Liam P.
Abstract: Objectives: To compare two modes (general and cricket-specific) of morning priming exercise on afternoon physical and cognitive performance, and subjective readiness to perform in professional male cricketers. Design: Randomised, crossover, counterbalanced. Methods: On three occasions, 16 professional men's cricketers completed afternoon tests of countermovement jump height, cricket-specific sprint performance (running between the wickets, two runs), cognitive function (Stroop test, time taken), and subjective readiness to perform. Control (CON; passive rest), lower-body resistance exercise priming (LIFT; trap bar deadlifts, 6 × 4 repetitions up to 85% of one repetition maximum), or cricket-specific running priming (RUN; 6 × 35.36 m sprints including a 180° change of direction) interventions were implemented 5.5 h before testing. Results: Afternoon sprint times were faster in RUN (−0.04 s, p = 0.013) and LIFT (−0.07 s, p < 0.001) versus CON, and faster in LIFT than RUN (−0.03 s, p = 0.032). Jump height (+1.1 cm, p = 0.021) and cognitive function (−3.83 s, p = 0.003) were greater in LIFT than CON, whilst RUN outperformed CON for cognition (−2.52 s, p = 0.023). Although perceived readiness was not influenced by trial ( p > 0.05), players reported favourable responses on the "aggression" subscale in LIFT relative to CON (+1 arbitrary unit, p = 0.022). Conclusions: Both general (lower-body resistance exercise) and cricket-specific (simulated running between wickets) morning priming are effective match-day strategies to improve afternoon markers of physical and cognitive performance in professional men's cricketers. Practitioners may thus be afforded flexibility in situations where resistance exercise is not feasible on the morning of a match.